Fabrication and modeling of shape memory alloy springs. (10th November 2016) - Heidari, B; Kadkhodaei, M; Barati, M; Karimzadeh, F
Abstract: In this paper, shape memory alloy (SMA) helical springs are produced by shape setting two sets of NiTi (Ti-55.87 at% Ni) wires, one of which showing shape memory effect and another one showing pseudoelasticity at the ambient temperature. Different pitches as well as annealing temperatures are tried to investigate the effect of such parameters on the thermomechanical characteristics of the fabricated springs. Phase transformation temperatures of the products are measured by differential scanning calorimetry and are compared with those of the original wires. Compression tests are also carried out, and stiffness of each spring is determined. The desired pitches are so that a group of springs experiences phase transition during loading while the other does not. The former shows a varying stiffness upon the application of compression, but the latter acts as passive springs with a predetermined stiffness. Based on the von-Mises effective stress and strain, an enhanced one-dimensional constitutive model is further proposed to describe the shear stress–strain response within the coils of an SMA spring. The theoretically predicted force–displacement responses of the produced springs are shown to be in a reasonable agreement with the experimental results. Finally, effects of variations in geometric parameters on the axial force–displacement response of an SMA spring are investigated.